2011
DOI: 10.1002/pfi.20259
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating mind fitness through mindfulness training: Applied neuroscience

Abstract: Mindfulness reduces distress, promotes optimal health, improves attentional control, mental agility, emotional intelligence, and situational awareness. Stress management and cognitive performance in Marines who spent more hours practicing Mindfulness Based Mind Fitness Training were superior to those soldiers who practiced fewer hours. Students receiving mindfulness training without practice demonstrated no significant change. The literature suggests that mindfulness training designed to inform rather than to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Research on mindfulness in organizational literature has been increasing. Current research explores the positive impact of mindfulness interventions in relation to working memory, 29 workplace coping, 75 perceived stress and medical costs, 36 positive leadership development, 53 and employee stress and performance. 85 Research studies in dispositional mindfulness, an already present state of mindfulness without training or intervention in mindfulness, suggest correlations with leaders' mental well-being and reduced employee stress 10 and destructive leadership.…”
Section: Mindfulness In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on mindfulness in organizational literature has been increasing. Current research explores the positive impact of mindfulness interventions in relation to working memory, 29 workplace coping, 75 perceived stress and medical costs, 36 positive leadership development, 53 and employee stress and performance. 85 Research studies in dispositional mindfulness, an already present state of mindfulness without training or intervention in mindfulness, suggest correlations with leaders' mental well-being and reduced employee stress 10 and destructive leadership.…”
Section: Mindfulness In Organizationsmentioning
confidence: 99%
“…Mindfulness is an evidence-based practice within the clinical community with branches in sports medicine [25][26][27][28] and organizational effectiveness. 29 Mindfulness training has been found to decrease pain, 30 increase quality of life, 31 decrease depression, 32,33 decrease anxiety, 34 decrease workplace stress, 35,36 increase emotional regulation, 37,38 positively impact youth leadership development, 39 and positively assist in quality relationship management. 40 Researchers have suggested that mindfulness impacts resilience by improving posttraumatic psychological adjustment, 41 improving positive affect, 42,43 and preventing burnout.…”
Section: Introductionmentioning
confidence: 99%
“…The Be Well model (illustrated in Figure 1) puts the goal of cultivating a mindful workforce at its centre, and encircles the goal with five characteristics of a mindful workforce that have been extrapolated from the literature: focused, self-aware, resilient, connected and adaptable (Rettie, 2003; Tugade & Fredrickson, 2007; O’Connell, McNeely, & Hall, 2008; Dickenson, Berkman, Arch, & Lieberman, 2012; Vago & Silbersweig, 2012). The next circle identifies eight evidence-based strategies; specifically, savouring (Tugade & Fredrickson, 2007; Bryant, Chadwick, & Kluwe, 2011; Jose, Lim, & Bryant, 2012; Smith & Hollinger-Smith, 2015), visualisation and/or gratitude (Sheldon & Lyubomirsky, 2006; Waters, 2012); present moment awareness, intention/focus (Killingsworth & Gilbert, 2010; Heydenfeldt, Herkenhoff, & Coe, 2011; Froeliger, Garland, & McClernon, 2012; Kok & Singer, 2016), empathy (Shapiro, Schwartz, & Bonner, 1998; Block‐Lerner, Adair, Plumb, Rhatigan, & Orsillo, 2007; O’Connor et al, 2015), physical activity such as yoga (Froeliger, Garland, & McClernon, 2012; de Manincor et al, 2015) and breath regulation (Jerath, Edry, Barnes, & Jerath, 2006; Cameron et al, 2011; Froeliger, Garland, & McClernon, 2012).…”
Section: About Worklife Wellnessmentioning
confidence: 99%
“…Once learners have been introduced to the practice, they can seamlessly integrate the steps into their day. A somatic approach to learning embodies a whole‐body approach to learning, one that recognizes multiple ways of knowing and positive disruption of typical learning patterns to allow for emerging possibilities (Heydenfeldt, Herkenhoff, & Coe, ; Lupberger, ; Schuyler, ). As we build on the literature to include some of our current practices to support greater collaboration with learners, we include our recent thinking and experiments that we intentionally introduce into the classroom.…”
Section: Using Mindfulness As Our Guiding Framework—abstract Conceptumentioning
confidence: 99%